Fast, downstream removal of photoresist using reactive oxygen species from the effluent of an atmospheric pressure plasma Jet. (4th March 2016) - West, A; van der Schans, M; Xu, C; Cooke, M; Wagenaars, E
Abstract: In the semiconductor industry the plasma removal of photoresist (PR) between processing steps (so-called plasma ashing) is a critical issue in enabling the creation of advanced wafer architectures associated with the next generation of devices. We investigated the feasibility of a novel atmospheric-pressure plasma jet (APPJ) to remove PR. Our device operates at atmospheric pressure, eliminating the need for low-pressure operation used in conventional plasma ashing. Also, our method uses the downstream effluent of the source, avoiding issues relating to ion bombardment, a known hinderance to atomic precision manufacturing. Two-photon absorption laser induced fluorescence (TALIF) measurements of the system has shown that the PR removal rate is directly correlated with the atomic oxygen flux to the surface. The maximum removal rates achieved were 10 μ m min −1, a factor of 100 improvement over typical low-pressure methods, while the quality of the etch, as assessed by attenuated total reflection fourier transform infrared spectroscopy, was found to be equal to low-pressure standards.